Prevalence and Risk Factors Associated with Hyperuricemia in the Pearl River Delta, Guangdong Province, China - Liu W; Liu W; Wang S; Tong H; Yuan J; Zou Z; Liu J; Yang D; Xie Z (Dove Medical Press, 2021)
Weiqi Liu,1,* Weiling Liu,2,* Shaoling Wang,3 Huichun Tong,4 Jianmin Yuan,5 Zhenning Zou,6 Jianwen Liu,7 Donghai Yang,8 Zhongxing Xie9 1Department of Clinical Laboratory, Maternal and Children Health Care Hospital (Huzhong Hospital) of Huadu, Guangzhou, Guangdong, 510800, People’s Republic of China; 2Department of Clinical Laboratory, Chancheng Centre Hospital, Foshan, Guangdong, 528000, People’s Republic of China; 3Department of Clinical Laboratory, Taishan People’s Hospital, Jiangmen, Guangdong, 529200, People’s Republic of China; 4Department of Clinical Laboratory, Boai Hospital of Zhongshan, Zhongshan, Guangdong, 528402, People’s Republic of China; 5Department of Clinical Laboratory, Humen Hospital, Dongguan, Guangdong, 523899, People’s Republic of China; 6Department of Clinical Laboratory, Shenzhen Maternity & Child Healthcare Hospital, Shenzhen, Guangdong, 518028, People’s Republic of China; 7Department of Clinical Laboratory, Huiyang Sanhe Hospital, Huizhou, Guangdong, 516211, People’s Republic of China; 8Department of Clinical Laboratory, Sanzhao Town Health Center, Jinwan District, Zhuhai, Guangdong, 519040, People’s Republic of China; 9Department of Clinical Laboratory, The Second People’s Hospital of Zhaoqing, Zhaoqing, Guangdong, 526060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaoling Wang Email shaoling_w@hotmail.comBackground: In China, the prevalence of HUA in the Pearl River Delta (PRD) region of Guangdong Province has not been extensively investigated. Therefore, this study investigated the prevalence of HUA and its related factors among people aged 20– 99 years in nine cities in the PRD.Materials and Methods: We selected 6491 health check participants from 9 cities in the PRD and collected participants’ anthropometric and biochemical test results for a cross-sectional study. We included 6491 participants and assessed their blood pressure (BP), body mass index (BMI), total cholesterol (TC), triglycerides (TG), glucose (Glu) and serum uric acid (UA) to analyze the regional prevalence of HUA and its related factors. HUA was indicated when fasting serum UA level was > 420 μmol/L in men and > 360 μmol/L in women.Results: Overall prevalence of HUA in our cohort was 34.05%; prevalence was higher in men than in women (41.53% vs 26.14%, P < 0.001). Characteristics associated with HUA were hypertension (odds ratio (OR), 5.506; 95% confidence interval (CI), 4.402– 6.889), higher body mass index (BMI; OR: 1.746; 95% CI: 1.560– 1.954), age 31– 40 years (OR: 0.829; 95% CI: 0.706– 0.973), age 61– 70 years (OR: 1.434; 95% CI: 1.194– 1.722) and age ≥ 71 years (OR: 1.742; 95% CI: 1.397– 2.173). In all subjects, serum UA was positively correlated with Glu, TG and TC. After we adjusted for age, BMI and BP, multivariate logistic regression analysis showed that HUA risk factors were high TC (OR: 1.770; 95% CI: 1.459– 2.147) and TG (OR: 1.961; 95% CI: 1.632– 2.357) in men; and high Glu (OR: 1.508; 95% CI: 1.084– 2.099), TC (OR: 1.341; 95% CI: 1.084– 1.660) and TG (OR: 1.680; 95% CI: 1.290– 2.187) in women.Conclusion: The prevalence of HUA was relatively high in the PRD of Guangdong Province. Relevant governmental bodies should focus on early diagnosis, early treatment and early intervention.Keywords: hyperuricemia, uric acid, prevalence, cardiovascular diseases, risk